High-performance anion-exchange membrane water electrolysis. (1st February 2019) - Park, Ji Eun; Kang, Sun Young; Oh, Seung-Hyeon; Kim, Jong Kwan; Lim, Myung Su; Ahn, Chi-Yeong; Cho, Yong-Hun; Sung, Yung-Eun
Abstract: In this study, we developed high-performance anion-exchange membrane water electrolysis (AEMWE) by investigating various parameters. To enhance AEMWE performance, the effects of the membrane-electrode assembly (MEA) fabrication method, operating conditions, and MEA parameters were examined. As a result of the optimization and the use of FAA-3-50 and FAA-3-Br as the AEM and anion-exchange ionomer, respectively, AEMWE showed the highest performance reported thus far. Single-cell tests and electrochemical impedance spectroscopy results indicate that optimized AEMWE minimized the ohmic, charge-transfer, and mass transport resistances. Overall, by examining the AEMWE parameters, we were able to improve the electrochemical reactions, namely, the oxygen evolution reaction and hydrogen evolution reaction, and achieved outstanding performance.